Determinants of abortion views among reproductive age women in Georgia 2023–2024 - Madeline Chandler; Jasmin A. Darville; Stephanie M. Eick (PLoS ONE, 2025)
Background Abortion is a continually debated legislative issue in the United States. We aimed to assess opinions toward abortion access amongst reproductive age adult women in Georgia, a state where abortion is banned after the detection of embryonic cardiac activity (around 6 weeks). Methods Participants were enrolled in the cross-sectional Policies and Social Stress (PASS) Study (N = 177). Sociodemographic characteristics, political orientation, religious characteristics, county of residence, and abortion views were assessed using self-reported questionnaires. Regarding abortion views, participants were asked about their opinion on the legality of abortion generally, and at 6, 14, and 24 weeks. We used logistic regression to examine whether sociodemographic factors, political orientation, religious characteristics, and county of residence were associated with odds of thinking abortion should be legal or illegal for each weeks’ gestation. Results Most participants (84%) reported supporting the legality of abortion in all or most cases. Though, that support decreased for specific weeks’ gestation (6 Weeks: 76%; 14 Weeks: 60%; 24 Weeks: 31%). Conservatives and moderates had higher odds of thinking abortion should be generally illegal compared to liberals (odds ratio [OR]=10.2, 95% confidence interval [CI]=4.1–27.3). Those who attended religious services more often and those who resided outside of the Atlanta area were more likely to believe abortion should be illegal compared to reference groups (OR=7.2, 95% CI = 3.0–17.9; OR=6.0, 95% CI = 2.5–16.3, respectively). However, the differences between groups attenuated as the weeks of pregnancy increased. Conclusions In a sample of reproductive age women in Georgia, we observed that opinions regarding the legality of abortion were nuanced with regards to gestational age. Fewer participants supported abortion access after fetal viability (i.e., around 24 weeks). Further, attitudes differed mostly along political, religious, and geographic lines. Implications While 76% of adult women in our sample supported abortion access at six weeks of pregnancy, less than one-third supported abortion at 24 weeks of pregnancy. These findings suggest that Georgia’s state policy that limits abortion after six weeks’ gestation does not reflect the views of the women in our sample.